The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1039/c4cp03462g
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric, calorimetric and mesophase properties of 1′′-(2′,4-difluorobiphenyl-4′-yloxy)-9′′-(4-cyanobiphenyl-4′-yloxy) nonane: an odd liquid crystal dimer with a monotropic mesophase having the characteristics of a twist-bend nematic phase

Abstract: This paper reports a novel liquid crystal phase having the characteristics of a twist-bend nematic phase formed by a non-symmetric ether-linked liquid crystal dimer. The dimer 1''-(2',4-difluorobiphenyl-4'-yloxy)-9''-(4-cyanobiphenyl-4'-yloxy) nonane (FFO9OCB) exhibits two liquid-crystalline phases on cooling at a sufficiently high rate from the isotropic phase. The high temperature mesophase has been reported in the literature as nematic and confirmed in this study. The other mesophase is metastable and can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
102
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 86 publications
(112 citation statements)
references
References 67 publications
5
102
0
Order By: Relevance
“…29 As for the experimental determinations of the bend elastic constant over the uniform nematic phase of twist-bend liquid crystal dimers, it is observed that the bend elastic constant decreases as temperature decreases on approaching the N-N TB phase transition, leading to small values at the phase transition but increasing slightly or being nearly temperature independent before N TB is reached. 25,[30][31][32] In addition, very recently Yun et al 33 have tried to measure K 3 in the N TB phase of CB7CB showing anomalous and positive values.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 As for the experimental determinations of the bend elastic constant over the uniform nematic phase of twist-bend liquid crystal dimers, it is observed that the bend elastic constant decreases as temperature decreases on approaching the N-N TB phase transition, leading to small values at the phase transition but increasing slightly or being nearly temperature independent before N TB is reached. 25,[30][31][32] In addition, very recently Yun et al 33 have tried to measure K 3 in the N TB phase of CB7CB showing anomalous and positive values.…”
Section: Introductionmentioning
confidence: 99%
“…The components of the mixtures, for which experimental results are reported, are the classic compound CB7CB and 1 00 -(2 0 ,4-difluorobiphenyl-4 0 -yloxy)-9 00 -(4-cyanobiphenyl-4 0 -yloxy)nonane (hereafter referred to by the acronym FFO9OCB) which has recently been shown to exhibit a monotropic N TB -phase. 32 Measurements are also reported of the splay (K 1 ) and bend (K 3 ) elastic constants in the conventional nematic phase for the pure compounds and some selected mixtures, as a function of both temperature and mole fraction. These experimental results provide further insight into the nature of the N TB -N phase transition, and the validity of our proposed model used to describe the phase transition.…”
Section: Introductionmentioning
confidence: 99%
“…Bend angles were taken to be the all‐ trans conformer that we found to be dominant using solution‐based 1D 1 H NOESY NMR spectroscopy; indeed this is also reported to be the dominant conformer in the bulk N TB phase from 2 H NMR data coupled with DFT calculations 19. The dominance of the all‐ trans conformer over other conformations has been demonstrated for both methylene‐ and ether‐linked dimers using proton‐enhanced local field (PELF) NMR spectroscopy on CB7CB19 and dielectric spectroscopy on 1′′‐(2′,4‐difluorobiphenyl‐4′‐yloxy)‐9′′‐(4‐cyanobiphenyl‐4′‐yloxy)nonane (FFO9OCB), respectively 44. In reality the use of a single conformer to describe the bend angle is insufficient for flexible molecules, such as LC dimers, and so we opted to study a new set of materials computationally, obtaining a library of conformers from which we can then obtain the full distribution of bend angles as well as a weighted average molecular bend 45.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years there has been a resurgence of interest in liquid‐crystal dimers and bimesogens, driven by interest in wide temperature range blue phases,1, 2 flexoelectric behaviour3, 4, 5 and the ability of some dimeric materials to exhibit a lower‐temperature mesophase lacking lamellar organisation thereby being described as nematic 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18. This lower temperature ‘nematic’ phase is denoted N X or N TB ,6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18 in which ‘X’ and ‘TB’ refer to unknown and twist‐bend, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…This lower temperature ‘nematic’ phase is denoted N X or N TB ,6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18 in which ‘X’ and ‘TB’ refer to unknown and twist‐bend, respectively. The local structure of the N X /N TB phase is still hotly debated, with the heliconical ‘twist‐bend’ model proposed independently by Meyer19 and Dozov20 supported by 2 H NMR studies, measurement of the electroclinic effect, freeze‐fracture transmission electron microscopy (FFTEM) and carbon K‐edge SAXS 21, 22, 23, 24.…”
Section: Introductionmentioning
confidence: 99%